2015
DOI: 10.1371/journal.pone.0134910
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profile in the Liver of BALB/c Mice Infected with Fasciola hepatica

Abstract: Background Fasciola hepatica infection still remains one of the helminthic neglected tropical diseases (NTDs). It has a huge worldwide distribution, affecting mainly cattle and, sometimes, human beings. In addition to data reported about the immunological response induced by helminthic infections and that induced by Fasciola hepatica, little is known about the gene expression profile in its organ target, the liver, which is where adult worms are established and live for long periods of time, causing its charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 44 publications
1
17
1
Order By: Relevance
“…Transcriptomic responses within macroscopic lesions of F. hepatica-infected liver at 8 weeks post infection (wpi) in sheep revealed that gene expression is highly regulated (Alvarez Rojas et al, 2015), consistent with comparable microarray studies of mice (Rojas-Caraballo et al, 2015). Several processes characteristic of acute fasciolosis and upregulated in response to the damage caused by the parasite were identified.…”
Section: Proteomic and Transcriptomic Analysis Of Host Responses To Fsupporting
confidence: 64%
“…Transcriptomic responses within macroscopic lesions of F. hepatica-infected liver at 8 weeks post infection (wpi) in sheep revealed that gene expression is highly regulated (Alvarez Rojas et al, 2015), consistent with comparable microarray studies of mice (Rojas-Caraballo et al, 2015). Several processes characteristic of acute fasciolosis and upregulated in response to the damage caused by the parasite were identified.…”
Section: Proteomic and Transcriptomic Analysis Of Host Responses To Fsupporting
confidence: 64%
“…The resultant uncontrolled and excessive production of IL‐1κ mediates several proinflammatory disorders with severe pathologic outcomes (37). The migration of F. he‐ patica through the host's liver results in significant tissue damage (38, 39), and the parasite's secretions can induce hepatocyte cell death (40, 41). Inflammation and fibrosis in the liver is typically associated with excessive NLRP3 inflammasome activity, culminating in hepatocyte destruction via pyroptosis and IL‐1β secretion (42).…”
Section: Discussionmentioning
confidence: 99%
“…Such outcomes lead to sustained activation of proinflammatory immune responses (34) and mediate pathologic events, such as TNF-induced cell death (42). However, the expression of genes involved in both the IFN and TNF signaling pathways is actually reduced in F. hepatica-infected liver tissue (38), and lysosomal cathepsin B activity is diminished (43). These observations imply that the NLRP3 inflammasome is not activated during F. hepatica infection.…”
Section: Discussionmentioning
confidence: 99%
“…We investigated the gene expression profile during early and late stages of Fasciola hepatica infection in BALB/c mice [1] . For this purpose, we have selected three experimental groups, each containing 3 mice.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…Data presented here belong to a time-course investigation of the gene expression profile in the liver of BALB/c mice infected with F. hepatica metacercariae at 7 and 21 days after experimental infection. The data published here have been deposited in NCBI's Gene Expression Omnibus and are accessible through GEO Series accession number GSE69588 , previously published by Rojas-Caraballo et al (2015) in PLoS One [1] .…”
mentioning
confidence: 99%